A newly recorded species \(Zingiber densissimum\) (sect. \(Cryptanthium\)) for the flora of Vietnam - Le, Chi Toan; Nguyen, Thi Lien Thuong; Nguyen, Hoang Tuan; Nguyen, Van Canh; Truong, Quang Cuong; Nguyen, Van Khuong; Pham, Thi Thanh Dat; Nguyen, Danh Duc (Academia Journal of Biology, 2023)
During our floristic expedition in South Vietnam, a wild taxon Zingiber densissimum (sect. Cryptanthium) was recognized as a newly recorded species for the flora of Vietnam. The taxonomic treatment with a description is provided, along with photographs, distribution, ecology, a conservation assessment, and morphological comparison with its alliance species. It is similar to Zingiber orbiculatum and Zingiber mioga in having whitish flowers and bright yellow anthers but differs in many aspects of vegetative and reproductive characteristics. Moreover, a taxonomic key for all species of sect. Cryptanthium in Vietnam is included.